Pelatihan Promosi Digital Pariwisata bagi Pelaku Desa Wisata Danau Lingkat, Jambi - Sri Hartati; Muchamad Fauzi Djamal; Rialdo Rezeky Manogari Lumban Toruan (Jurnal Pustaka Dianmas, 2026)
Lingkat Lake which is located in Kerinci regency, Jambi, is known as one of the tourist destinations that has natural beauty and biodiversity. The development of the Lingkat Lake tourist attraction is able to move the economy of the village community with the growth of a supporting business ecosystem such as lodging, restaurants, souvenirs, and transportation services. Although it has great potential, the digital promotion of Lingkat Lake tourism is still very minimal in publication. Digital promotion plays a role in disseminating information massively and creating spaces for interaction and expression. The tourism digital promotion training activity was held to improve the knowledge and skills of Lake Lingkat tourism village managers in designing and creating promotional content on social media. This training uses two approaches, namely a participatory approach and experiential learning to ensure a change in knowledge and understanding of the urgency of digital tourism promotion. The training activities were evaluated through pretest and posttest in the form of a structured questionnaire using a 5-level Likert scale. The results of the evaluation showed that there was an increase in participants' understanding and skills in digital tourism promotion activities. These findings prove that systematic and measurable training is able to increase the capacity and competence of participants in utilizing social media as a means of digital tourism promotion.